SAT0391 Musculoskeletal manifestations of chikungunya fever in elderly patients – chikbrasil cohort. (12th June 2018) - Dantas, A.; Duarte, A.; Marques, C.; Ranzolin, A.; Cavalcanti, N.; Medeiros, M.; Bezerra, M.; Marques, V.; Rocha, L.; Melo, P.; Valadares, L.; da Fonte, C.; et al.
Abstract : Background: Elderly patients with Chikungunya virus (CHIKV) infection may exhibit atypical and more severe clinical manifestations in the acute phase(, 1 but little is known about these patients progress in the chronic phase of the disease. Objectives: To describe the chronic clinical course of CHIKV infection in Brazilian elderly patients. Methods: The CHIKBRAZIL is a prospective, multicenter, observational cohort, conducted in six research rheumatology centres from the Northeast of Brazil, and has enrolled CHIK patients with joint manifestations since April 2016. 2 Data from 353 patients followed up to December 2017 were analysed, divided into two groups: the elderly (age ≥60 years) and not elderly. Results: Of the 353 cases, 124 were elderly (35, 1%), mean age was 67.1 years (±5.6), 81.5% women. Patients in the elderly group had a higher frequency of comorbidities, such as systemic arterial hypertension (p<0.0001), diabetes mellitus (p<0.001) and hyperlipidemia (p=0.0003). The median time of disease was 26 weeks, most of them were in the chronic phase of the disease (61.3%). With respect to initial clinical manifestations, no significant differences were observed between the groups, except for fatigue, which occurred more often in the non-elderly group (p=0.036). In general, the elderly group presented a lower frequency of absence at work (0.000), lower limb oedema (0.006) and less prescription of methotrexate (p=0.048). In addition, it was also observed that older patients had a lower mean of the number of painful joints (10.2±1.7), but without statistical difference (p=0.0655). After a median follow-up time of 27.5 weeks, the number of patients who presented complete improvement was higher in the non-elderly group (p=0.07), but without differences between the number of tender and swollen joints, persistence of arthralgia or arthritis in the two groups. No association was observed between the presence of comorbidities and the clinical evolution of the patients. Conclusions: Despite the risk of a more severe evolution at the onset of CHIKV infection, elderly patients present a similar clinical course to the non-elderly in the chronic phase, apparently with less severity. However, such group is a high-risk population with an important number of comorbidities. In all stages of the disease, especially in the acute phase, strict clinical supervision is recommended regarding the use of drugs and increased risk of complications. References: [1] Chopra A, Anuradha V, Ghorpade R, Saluja M. Acute Chikungunya and persistent musculoskeletal pain following the 2006 Indian epidemic: a 2-year prospective rural community study. Epidemiol Infect2012;140(5):842–50. [2] Marques CDL, Cavalcanti N, Luna M, et al. Chikungunya Fever Outbreak in Brazil: Preliminary Assessment in a Cohort of Patients with Rheumatological Manifestations. Arthritis Rheumatol [Internet]201620-nov-2016;68(S10). Disclosure of Interest: None declared